The optimum light wavelength and light intensity for the survival and growth of sutchi catfish, pangasianodon hypophthalmus (sauvage) juvenile - Nor Amira binti Yusoff (Kulliyyah of Science, International Islamic University Malaysia, 2019)
Light conditions affect the survival and growth of fish. However, there are limited studies regarding the effects of light wavelengths and light intensities to the fish. Sutchi catfish, Pangasianodon hypophthalmus (Sauvage, 1878) is an important fish species for aquaculture in Southeast Asia. Thus, this study aims to determine the optimum light wavelength and intensity for sutchi catfish juveniles culture based on the fish survival, specific growth rate for body length (SGRTL), specific growth rate for body weight (SGRBW), production index (PI), behaviour, and cortisol level (stress hormone) under these light conditions. Based on the results, there was no significant difference between light wavelengths and light intensities for the survival rate of the fish. For the effect of light wavelength, the results showed that SGRBW and SGRTL were significantly highest under red light wavelengths. The resting and biting activities were significantly lowest under red light wavelength. In the cortisol experiment, although the juveniles' cortisol level under red light wavelengths was slightly higher than the juveniles reared under blue and white light wavelength, it is suggested that the moderate increase in cortisol level promotes the juveniles feed intake; thus, increasing its growth rates. As for light intensity, the significant highest PI and lowest biting and resting activities were observed under 0.0014 µmol/m²/s. In conclusion, the light wavelength of red under the light intensity of 0.0014 µmol/m²/s is recommended for the rearing of the sutchi catfish juveniles. This result will be useful knowledge for seed production of sutchi catfish.